Improving The Quality of Public Poly Services At Bintaro Woman and Children Clinic Jagakarsa - Fembriya Tenny Utami; Andriyani Andriyani; Suherman; Abul A’la Al Maududi; Fini Fajrini (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
The quality of healthcare services is a crucial factor in improving community well-being. The General Clinic of Bintaro Woman and Children Clinic Jagakarsa must ensure that its service quality meets national standards.To identify strategies for improving the quality of services at the clinic.This study employed a qualitative approach using observation and interviews with seven informants, consisting of three patients, two doctors, and two non-medical staff. Data were analyzed using the Miles & Huberman technique, which includes data reduction, presentation, and conclusion drawing.Compliance with hand hygiene before patient contact was generally good; however, there were instances of negligence after removing personal protective equipment (PPE). PPE use adhered to policy, but glove usage was inconsistent, particularly when handling pediatric patients. Patient identification was carried out through document verification, although reliance on verbal communication alone sometimes reduced accuracy. Patient satisfaction was generally positive regarding registration, procedures, and service specifications, but complaints were raised about long waiting times, high costs, and unfriendly receptionist service.Routine training, policy reinforcement, regular evaluation, and improvements in time efficiency and cost transparency are necessary to enhance service quality and patient satisfaction.